FORM OF CODE MIX IN INDONESIAN LANGUAGE LEARNING STUDENTS GRADE VIII SMP NEGERI 1 AMBON - Novita Tabelessy; Nancy Umkeketony (JURNAL TAHURI, 2021)
Code mixing is a form of using other languages besides code over. According to Nababan (in Suandi, 2014:139) that code mixing is the mixing of two or more languages or different languages in a speech act or discourse without anything in the language situation that demands mixing the language. Code mixing occurs when a speaker using a language predominantly supports a speech inserted with other language elements. It is usually related to the characteristics of the speaker, such as social background, level of education, religious sense. The object of research is a form of code mixing that occurs in the interaction of online learning of Indonesian subjects. The study used is Sociolinguistic. This type of research is qualitative by using interview techniques, field recording, and direct observation on the form of code mixing in online learning interactions of Indonesian subjects involving subject teachers and grade VIII students of SMP Negeri 1 Ambon. The results of the study found there were 19 forms of code mixing in the interaction of Indonesian language learning students in grade VIII SMP Negeri 1 Ambon. Data in the field shows, too, that not only do students produce code mixes in interactions, but teachers also produce fragments of code mix in communicating. Code mixing that occurs unconsciously is generated more by students, than subject teachers